2012
DOI: 10.1111/dmcn.12019
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of hand sensation in adults with conservatively treated obstetric brachial plexus lesion

Abstract: OBPL Obstetric brachial plexus lesionAIM Sensory function is assumed to recover almost completely in obstetric brachial plexus lesion (OBPL), and is reported to recover much better than motor function. However, there is no obvious physiological reason why this should be so. Any persistent problems with sensory innervation might contribute to disability, therefore we aimed to assess sensory dysfunction in adults resulting from OBPL.METHOD Adults with conservatively treated OBPL (n=17; 12 females, five males; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…6,13,14 Co-contraction in OBPL might also be due to disturbed central motor programming, owing to factors such as deafferentation, 15 misrouting, and the fact that the lesion occurs before motor programmes have been developed fully. 5,6,16 Peripheral factors may, therefore, be involved in co-contraction in addition to central factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,13,14 Co-contraction in OBPL might also be due to disturbed central motor programming, owing to factors such as deafferentation, 15 misrouting, and the fact that the lesion occurs before motor programmes have been developed fully. 5,6,16 Peripheral factors may, therefore, be involved in co-contraction in addition to central factors.…”
Section: Discussionmentioning
confidence: 99%
“…A flow chart indicating the numbers of potentially eligible participants, those examined for eligibility, confirmed eligible, and those included in the study, was published in a previous paper. 15 The protocol was approved by the Medical Ethics Committee of the Leiden University Medical Center. All participants provided informed consent.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Axons that successfully pass the neuroma in continuity are likely to end up in a different basal lamina tube from the original. This process is called misrouting and may cause the phenomenon of cocontraction [37]. Root avulsion, the most severe type of lesion, is a total disconnection between peripheral nervous system and the spinal cord.…”
Section: Obstetrical Brachial Plexus Injurymentioning
confidence: 99%
“…Moreover, adults with OBPP have reported many problems, including pain, impaired sensation, and limitation of function, which interfered with activities of daily living. 3 For these reasons, the study of adults with conservatively managed OBPP by Anguelova et al 4 is timely, and suggests that the commonly held view that sensory recovery is good in people with OBPP should be revised. A systematic investigation by this group of sensory function in adults with OBPP has shown that sensory discrimination, assessed using Semmes-Weinstein monofilaments and two-point discrimination, was worse in people with OBPP than in a comparison group.…”
mentioning
confidence: 99%